2015
DOI: 10.1108/cgij-03-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Nursing experiences of clinical governance implementation: a qualitative study

Abstract: Purpose -Clinical governance (CG) was used as a driver to improve safety and quality of healthcare. CG implementing is a change in health system and all the stakeholders must be participating. The purpose of this paper is to study nurses' experience about CG movement in Tabriz hospitals. Design/methodology/approach -A qualitative study using Focus Group Discussions (FGD) was done. Purposeful Sampling was used to select the objectives including 65 participants. Actually seven FGD's were held. Content analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…Bahadori et al reported that focusing too much on documentation is one criticism leveled against the Iranian accreditation process [34]. In another study, nurses considered documentation boring, stressful, and an extra activity [35]. Intelligent computer systems, unifying and integrating policies and protocols by staff in academic centers, and decreases in extra bureaucracy can reduce documentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bahadori et al reported that focusing too much on documentation is one criticism leveled against the Iranian accreditation process [34]. In another study, nurses considered documentation boring, stressful, and an extra activity [35]. Intelligent computer systems, unifying and integrating policies and protocols by staff in academic centers, and decreases in extra bureaucracy can reduce documentation.…”
Section: Discussionmentioning
confidence: 99%
“…As a number of variables have been loaded onto more than one factor, therefore, at this stage, for ease of interpretation of data, variables that had a moderate factor-loading on different factors, that is, on more than one factor, were eliminated one by one. During the three phases of factor analysis, nine variables including variables 7,8,18,20,25,28,29,35, and 36 from the sum of variables were eliminated, and the factor analysis test was performed again with 31 remaining variables. Finally, a six-factor model with 31 variables was extracted that explained 63.20% of the variance of the data.…”
Section: Sample Demographicsmentioning
confidence: 99%
“…Studies were published between 2013 and 2017. Three studies [33, 36, 38] were carried out in the northern part of Iran (Tehran province), while 5 and 2 studies were performed in the centre [30–32, 37, 39] (Isfahan, Kerman and Yazd provinces) and in the west [34, 35] (Qazvin and Tabriz provinces) of Iran, respectively. Eight studies conducted semi-structured interviews, 1 study performed focus groups and the remaining studies performed both semi-structured interviews and focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…In health care organizations with a positive safety culture, especially hospitals, each of individuals gives priority to patient safety and obtains the knowledge and skills necessary to reduce risks . Hospitals use different programs and techniques to promote the safety culture, but unfortunately, they do not achieve their goals, mainly due to lack of leadership participation . A useful technique for senior executives' participation is to meet and talk their frontline staff while they are working.…”
Section: Introductionmentioning
confidence: 99%
“…5 Hospitals use different programs and techniques to promote the safety culture, but unfortunately, they do not achieve their goals, mainly due to lack of leadership participation. [6][7][8] A useful technique for senior executives' participation is to meet and talk their frontline staff while they are working. In this technique, managers and frontline staff collaborate to identify and resolve barriers to productivity, quality, and safety.…”
Section: Introductionmentioning
confidence: 99%